Discontented miracle : growth, conflict, and institutional adaptations in China - Yang, Dali L. (Series on contemporary China, 2007)
China has been enjoying stellar economic growth for more than a quarter of a century. Yet the rapid growth amid market-oriented reforms has not been an unalloyed blessing. The?China Miracle? has been accompanied by soaring income inequality and rising social tensions, over-taxing China?s resource base and contributing to an environmental crisis. Despite substantial improvement in the standard of living and other social indicators, China?s leaders have, in the aftermath of the Tiananmen crackdown, steadfastly held back the opening up of the political system. In this volume, contributors from t.